2022
DOI: 10.1007/s00044-021-02832-4
|View full text |Cite
|
Sign up to set email alerts
|

Isatin derivatives as broad-spectrum antiviral agents: the current landscape

Abstract: In recent decades, several viruses have resulted in large outbreaks with serious health, economic and social consequences. The current unprecedented outbreak of the new coronavirus, SARS-COV-2, necessitates intensive efforts for delivering effective therapies to eradicate such a deadly virus. Isatin is an opulent heterocycle that has been proven to provide tremendous opportunities in the area of drug discovery. Over the last fifty years, suitably functionalized isatin has shown remarkable and broad-spectrum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 119 publications
0
18
0
Order By: Relevance
“…13 C signals at 19.93 (16) and 55.76 (17) ppm verified the presence of the coordinated ethyl alcohol. The signal at 13.00 ppm showed that the S CH 3 (7) group in the starting material was protected, whereas the CH N ( 8) and O CH 3 (13) carbons of the aldehyde added by the template reaction were observed at 159.92 and 56.14 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C signals at 19.93 (16) and 55.76 (17) ppm verified the presence of the coordinated ethyl alcohol. The signal at 13.00 ppm showed that the S CH 3 (7) group in the starting material was protected, whereas the CH N ( 8) and O CH 3 (13) carbons of the aldehyde added by the template reaction were observed at 159.92 and 56.14 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on isatin thiosemicarbazones, favorite compounds of the subject, have provided an important contribution to the purpose of reaching an antiviral ingredient, and some of them have also been examined for human immunodeficiency viruses (HIVs). [3][4][5][6][7] Some of the other notable thiosemicarbazones are those derived from acetylpyridine, [8,9] pyridazine, [10] and α-amino acids. [11] Further, it was shown that platinum-and palladium-containing thiosemicarbazones have antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin-based thiosemicarbazones are also among the derivatives of this type of isatin [1]. They also demonstrate the abundant and versatile reactivity of thiosemicarbazones while giving this such compound framework interesting biological activities, such as antiviral [12], antimycobacterial [13], anticancer [14], antibacterial [15], antifungal [16], anti-in ammatory [17], Alzheimer's [18], and antitumor [19] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 30 oxindole derivatives computed, only four hits showed a strong binding affinity and low energy; interestingly, one hit of those leads was designed and synthesized by Barakat et al [ 15 ]. A recent study concluded about the potential scope of isatin derivatives for SARS-CoV-2 as protease inhibitors [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Therefore, to discover this spirooxindole scaffold as being anti-coronavirus is quite interesting.…”
Section: Introductionmentioning
confidence: 99%